Design and development of a 3D-printed balloon type actuator for a hybrid force-display glove. (19th January 2022) - Koyanagi, Ken'ichi; Takata, Daisuke; Tamamoto, Takumi; Noda, Kentaro; Tsukagoshi, Takuya; Oshima, Toru
A balloon actuator is a type of pneumatic actuator developed for a virtual reality-based hand rehabilitation device, which is a hybrid force-display glove that combines an actuator and passive element. A balloon actuator typically generates a strong force and is safe for hand rehabilitation; however, the actuator has slow response characteristics for force display applications that use virtual reality techniques. Herein, we demonstrate an improved balloon actuator that features a 3D-printed inner construction optimised for glove type force display device with a soft material, and the basic and force display characteristics of the 3D-printed balloon actuator. The 3D-printed balloon actuator shows the force display characteristics by representing VR objects at an acceptable level.